Intergeneric Hybridization between Phalaenopsis 2166 and Vanda ‘saint valentine’: Characterization of Parents Using ndhE cpDNA Partial Sequence - Murni Dwiati; Agus Hery Susanto (Universitas Gadjah Mada, 2021)
An intergeneric cross between Phalaenopsis 2166 and Vanda ‘saint valentine’ has successfully produced protocorms that will be grown further to form seedlings. The present study aims to genetically characterize both parents by using ndhE partial gene as its sequence is shown polymorphic among five orchid genera of the subtribe Oncidiinae. The results reveal that the ndhE partial sequences of Phalaenopsis 2166 and Vanda ‘saint valentine’ are considerably homologous with those of Oncidium. However, alignment of ndhE partial sequences between both parents shows only 58% similarity, leading to the conclusion that a relatively high genetic difference between them may occur.